2002
DOI: 10.1021/cm020391b
|View full text |Cite
|
Sign up to set email alerts
|

New Polylactide/Layered Silicate Nanocomposites:  Role of Organoclays

Abstract: In the preparation of polymer/clay nanocomposites, organoclay plays an important role in lipophilizing and dispersing the clay into less polar polymer matrixes. Organic modifiers of various chain lengths were examined in different types of clays, smectite, montmorillonite (MMT), and mica, to prepare their corresponding organoclays. The layered structure and gallery spacing of organoclays and polylactide (PLA) nanocomposites shows that, with a modifier of the same chain length, the gallery spacing of the organo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
261
1
4

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 396 publications
(272 citation statements)
references
References 23 publications
6
261
1
4
Order By: Relevance
“…119,120 Thus, PLA was melt compounded in a TSE at 1908C with MMT, ''smectite'' and FM-all pre-intercalated with quaternary phosphonium bromides (e.g. tri-butylhexadecyl phosphonium bromide 3BHDP).…”
Section: Biodegradable Polyesters: Polylactic Acid (Pla) Polycaprolamentioning
confidence: 99%
“…119,120 Thus, PLA was melt compounded in a TSE at 1908C with MMT, ''smectite'' and FM-all pre-intercalated with quaternary phosphonium bromides (e.g. tri-butylhexadecyl phosphonium bromide 3BHDP).…”
Section: Biodegradable Polyesters: Polylactic Acid (Pla) Polycaprolamentioning
confidence: 99%
“…Nanoclays would decrease oxygen transmission rate (Shina Ray et al 2003) (Maiti et al 2002). Consequently, less oxygen in the system results in minimization of undesirable effects on meat products like oxidation of lipids, loss of exudates, loss of texture and development of liver-like flavours (Ahvenainen 2003).…”
Section: Key Assumptionsmentioning
confidence: 99%
“…Such properties are related to the volume fraction, shape and size of the filler particles. Following the pioneering work of Toyota researchers on a nylon 6-clay nanocomposite in the early 1990s [43,47,48], well-exfoliated nanocomposites have been produced in various nylons [44,[49][50][51], polystyrene [52], certain polyimides [53], polypropylene [54][55][56][57], polylactide [58,59] and epoxies [60][61][62]. These studies showed that the improvement in the mechanical performances of nanocomposites mainly originated from the nanosize dimensions of silicates (as this results in an extremely large aspect ratio) and from strong polymer-filler interactions that might affect the effectiveness of the load transfer between the silicate layers and polymer matrix.…”
Section: Mechanical Properties Of Nanocompositesmentioning
confidence: 99%